Effects of coeliacomesenteric blood flow reduction on intestinal barrier function in rainbow trout Oncorhynchus mykiss. Issue 3 (26th September 2018) - Sundh, Henrik; Gräns, Albin; Brijs, Jeroen; Sandblom, Erik; Axelsson, Michael; Berg, Charlotte; Sundell, Kristina
Abstract : The aim of the current work was to elucidate if there is a connection between stress‐induced decrease in coeliacomesenteric artery blood flow ( i.e . gastrointestinal blood flow; GBF) and disruption of the intestinal primary barrier in rainbow trout Oncorhynchus mykiss . Upon initiation of a 15 min acute chasing stress, the GBF decreased instantly by c . 92%. The GBF then slowly increased and reached c . 28% of resting values at the end of the stress protocol. After the stress was ceased, the GBF slowly increased and returned to resting values within c . 45 min. Intestinal permeability assessment in an Ussing‐chambers set‐up revealed impaired intestinal barrier function 24 h after stress. When the stress‐induced GBF reduction was mimicked by an experimental occlusion of the coeliacomesenteric artery for 15 min followed by 24 h recovery, no effect on intestinal barrier function was observed. These results suggest that no direct causal relationship can be found between the GBF reduction and development of intestinal barrier dysfunction following periods of acute stress in this species of fish.